Implementasi Perda Kota Probolinggo No 189 Tahun 2019 Dalam Pelestarian Kesenian Jaran Bhodag Dari Prespektif Culture Value - Sucahyo, Imam; Putri, Vero Maharani; Pamungkas, Prayogo Bayu; Prasetyo, Adi; Septiawan, Indra; Ulum, Khoirul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
traditional arts, particularlyDot Some people and kids are starting to lose interest in and abandontraditional dances. Traditional dance formsmight disappear if no one is interested in them. Because children arebecoming more interested in learning modern dances now that there areso many of them. Jaran Bhodag Dance is one of the folk dances. TheJaran Bhodag dance is a typical dance from the city of Probolinggo thatstill exists and participates in competitions or events about the JaranBhodag dance in the middle of modern times. This phenomenon serves asthe foundation for this study's formulation of the issue, which is todetermine how the Sawunggaling Ethnic Collaboration Studio hasmanaged to keep the Jaran Bhodag dance alive up to this point and whatchallenges it hasencountered. The study is being conducted at the Sawunggaling EthnicCollaboration Studio in Probolinggo, East Java. Descriptive with aqualitative approach is the research methodology used. using interviewsand observation, two methods for gathering data. The study's findingsrevealed that the sawuggaling ethnic collaboration studio has a strategyto uphold the shared values that are ingrained in society, theorganization's mission, or the local environment. These values have theirroots in customs, traditions, and symbols, and have distinct qualities thatcan be used as a guide for behavior and reactions to what will occur oris occurring. The Sawunggaling Ethnic Collaboration Studio's tacticsinclude teaching techniques, advertising, and competitions orperformances. The Sawunggaling Ethnic Collaboration Studioencounters challenges, which can be categorized as internal challengeslike staffing shortages and space issues, and external challenges like theentry of other cultures and the availability of a wide range ofcontemporary dance. The existence of Jaran Bhodag Dance Arts andcultural values, which cannot be separated from norms and ways ofacting that influence attitudes and reactions to events and variousexamples of social phenomena in a cultural context, can be strengthenedby supporting factors such as parental participation, numerous events,and activities. The research problem faced is the difficulty of finding anidea that is truly valid about the history of the Jaran Bhodag because ofdifferences in opinion from each source, some of whom work as artists